Biochar reduced the mineralization of native and added soil organic carbon: evidence of negative priming and enhanced microbial carbon use efficiency - Kalu, Subin; Seppänen, Aino; Mganga, Kevin Z.; Sietiö, Outi-Maaria; Glaser, Bruno; Karhu, Kristiina (Biochar (Online), 2024)
Biochar has been widely recognized for its potential to increase carbon (C) sequestration and mitigate climate change. This potential is affected by how biochar interacts with native soil organic carbon (SOC) and fresh organic substrates added to soil. However, only a few studies have been conducted to understand this interaction. To fill this knowledge gap, we conducted a 13 C-glucose labelling soil incubation for 6 months using fine-textured agricultural soil (Stagnosol) with two different biochar amounts. Biochar addition reduced the mineralization of SOC and 13 C-glucose and increased soil microbial biomass carbon (MBC) and microbial carbon use efficiency (CUE). The effects were found to be additive i.e., higher biochar application rate resulted in lower mineralization of SOC and 13 C-glucose. Additionally, soil density fractionation after 6 months revealed that most of the added biochar particles were recovered in free particulate organic matter (POM) fraction. Biochar also increased the retention of 13 C in free POM fraction, indicating that added 13 C-glucose was preserved within the biochar particles. The measurement of 13 C from the total amino sugar fraction extracted from the biochar particles suggested that biochar increased the microbial uptake of added 13 C-glucose and after they died, the dead microbial residues (necromass) accumulated inside biochar pores. Biochar also increased the proportion of occluded POM, demonstrating that increased soil occlusion following biochar addition reduced SOC mineralization. Overall, the study demonstrates the additional C sequestering potential of biochar by inducing negative priming of native SOC as well as increasing CUE, resulting in the formation and stabilization of microbial necromass. Graphical Abstract Highlights Biochar showed additional C storage ability by preserving SOC from mineralization (negative priming) and stabilizing added labile organic substrate Biochar (30 Mg ha −1 ) significantly increased microbial carbon use efficiency Biochar increased the formation of stable microbial residues (necromass) from a labile substrate (glucose) added to soil, as indicated by 13 C recovery in amino sugars